2019
DOI: 10.17323/jle.2019.9726
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Collaborative Note-Taking in Flipped Learning Contexts

Abstract: While the benefits of shared note-taking during live lectures have been studied, the effects of shared note-taking in e-learning environments merit examination since such courses often feature asynchronous video lectures, allowing students to work together to construct notes over longer periods of time. A study (n=92) was conducted in the context of a flipped scientific writing course at a Korean university to investigate the effects of collaborative online note-taking on student learning. Students in the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…In an asynchronous online learning environment, Balwin et al (2019) saw better learning outcomes for group note-takers than those in the control group, who were advised to take notes individually. However, a key limitation in both of the studies (Baldwin et al, 2019;Orndorff, 2015) is that the researchers only monitored and examined the collaborative note-taking documents. Consequently, it is unknown how much note-taking members of the control group actually did.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In an asynchronous online learning environment, Balwin et al (2019) saw better learning outcomes for group note-takers than those in the control group, who were advised to take notes individually. However, a key limitation in both of the studies (Baldwin et al, 2019;Orndorff, 2015) is that the researchers only monitored and examined the collaborative note-taking documents. Consequently, it is unknown how much note-taking members of the control group actually did.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To do so, participants were divided into two groups, with one group taking notes individually and the other taking notes collaboratively in small groups. As prior experimental studies on collaborative note-taking (Baldwin et al, 2019;Orndorff, 2015) have not monitored the amount of notes that were taken in the control (non-collaborative) condition, in the present study, students' online note-taking documents from the individual and collaborative note-taking conditions were created and monitored by the course instructor. In this way, the amount of notes taken by students from each condition could be assessed.…”
Section: The Present Studymentioning
confidence: 99%
“…Students may divide the labor of note-taking as well to produce a more detailed set of notes than they would otherwise have made by themselves (Jansen et al, 2017). Furthermore, the ability for students to focus on particular parts of the contents and the processes inherent in collaborative note-taking may lead to students gaining a better understanding of the contents (Baldwin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While there has been a lack of research into collaborative note-taking, two controlled experiments found that students who actively took notes collaboratively showed improved learning performance compared to those who took notes individually (Baldwin et al, 2019;Orndorff, 2015). The common explanation in these two studies was that the students seemed to benefit from sharing the workload of note-taking so that they were better able to focus on the lecture being presented.…”
Section: Introductionmentioning
confidence: 99%
“…Literature pertaining to online collaborative learning strongly suggests that taking notes together allows students in online courses to collaborate and has a significant effect on students' learning development by enabling them to construct a meaningful context (Baldwin et al, 2019). Consequently, optimizing the implementation of note-taking is an effective strategy to assist in constructing shared knowledge in an online learning environment.…”
Section: Introductionmentioning
confidence: 99%